Main Stages and Regularities of Coast Formation of Large Plain Reservoirs - Дубняк, С. С. (Київський національний університет імені Тараса Шевченка, 2021)
The main stages of the reservoir coast formation and their typological characteristics are considered on the base of the analysis of long-term monitoring studies of the Dnieper reservoirs coast dynamics, as well as generalization of published materials on other large plain reservoirs. It is shown that the common scheme of periodization of the shoreline development manifested itself only in the two stages: abrasion and abrasion-accumulative leveling, and therefore it is premature to claim the general stabilization of the coast formation process. The conventionality of the dynamic equilibrium stage for the coast of reservoirs and the growing role of coastal currents and associated sediment flows and dynamic coast systems are noted. The current state of the coasts of large plain reservoirs is estimated as the beginning of the stabilization phase on the coasts with sufficient sand materials. On the coasts composed of loess, clay or loams the processes of intensive transformation are continued. The analysis of the direction of development of the coastal zone showed three stages of change of shore profile and plan: intensive formation, stabilization and the final stage of attenuation according to the leading factors. Active accumulation means the transition to the stage of abrasion-accumulative leveling, and the emergence of dynamic coast systems and activation of coastal sediment flows means the transition to the dismemberment of the shoreline by accumulative forms. The main regularities of development of coast formation processes – heredity, direction, inertia and variability are analyzed. The heredity means that the geographical and geological conditions which developed before the filling of the reservoir are played the leading role in these processes. The direction of development is associated with an increase of the erosion base and its consequence – the leveling of the coastal zone relief. The orientation of the general process of coast formation to achieve a state of dynamic equilibrium includes stages of inertia and variability. Inertial states are the certain periods when a certain set of factors and conditions and corresponding to them type of coast prevails. Variability is a change in factors and conditions, as a result of which new types of shores or fluctuations in the characteristics of the coastal zone (movement of shoals and dynamic coastal systems, seasonal changes in shore profiles) are formed.

На основі аналізу багаторічної динаміки розвитку берегів дніпровських та інших великих рівнинних водосховищ розглянуті основні стадії формування берегів і відповідні їм типологічні характеристики. Показано роль вихідного рельєфу і геологічної будови річкової долини в розвитку берегових процесів. Відзначено умовність стадії динамічної рівноваги для берегів водосховищ і зростаючу роль вздовжберегових течій і пов’язаних з ними потоків наносів і динамічних систем берегів. Проаналізовано основні закономірності процесів формування берегів – спадковість, спрямованість, інерційність і мінливість розвитку.
Основні стадії та закономірності формування берегів великих рівнинних водосховищ
Keywords: водосховище; берегова зона; стадії розвитку; абразійно-акумулятивні процеси; динамічні системи берегів; спадковість і спрямованість процесу; reservoir; coastal zone; stages of development; abrasion-accumulative processes; dynamic coastal systems; heredity and direction of the process